2017
DOI: 10.18632/oncotarget.15835
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of single nucleotide polymorphisms in genes of cell cycle and NF-κB pathways on the efficacy and acute toxicities of radiotherapy in patients with nasopharyngeal carcinoma

Abstract: Radiotherapy is one of the primary choices for the treatment of nasopharyngeal carcinoma (NPC) and may result in severe radiotoxicities on normal tissues. Single nucleotide polymorphisms (SNPs) in genes of cell cycle and NF-κB pathways have been linked with the prognoses of various cancers. The aim of this study was to explore whether SNPs of genes involved in cell cycle and NF-κB pathways are associated with responses to radiotherapy in NPC patients. We selected 3 SNPs in cell cycle pathway and 5 SNPs in NF-κ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Function annotation and KEGG pathway enrichment analysis showed that these up-regulated genes were mainly involved in cell division, cell cycle, DNA replication, cell proliferation and p53 signaling pathway, while the down-regulated genes were mainly enriched in cilium movement, motile cilium assembly, Huntington's disease, inner and outer dynein arm assembly. Recent studies indicated that single nucleotide polymorphisms in genes of cell cycle pathway and NF-κB pathway can potentially predict the clinical responses to radiotherapy for NPC patients [ 11 ]. These results were consistent with the fact that cancer development and progression are closely related to the defective function of cell cycle and cell proliferation regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Function annotation and KEGG pathway enrichment analysis showed that these up-regulated genes were mainly involved in cell division, cell cycle, DNA replication, cell proliferation and p53 signaling pathway, while the down-regulated genes were mainly enriched in cilium movement, motile cilium assembly, Huntington's disease, inner and outer dynein arm assembly. Recent studies indicated that single nucleotide polymorphisms in genes of cell cycle pathway and NF-κB pathway can potentially predict the clinical responses to radiotherapy for NPC patients [ 11 ]. These results were consistent with the fact that cancer development and progression are closely related to the defective function of cell cycle and cell proliferation regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding EC, previous studies have also confirmed the increased risk of cancer for both the Arg allele in TP53 rs1042522, as well as the combination GG and Arg-Arg variants in MDM2 and TP53 SNPs (10,11). The C allele of P14ARF rs3088440 has been found to be associated with the repression of CDKN2A, while the A allele with an impaired binding of miR-663b to the CDKN2A 3'UTR, and therefore with elevated expression of p14/p16 proteins (31)(32)(33)(34). The P14ARF rs3731217 polymorphism has been suggested to regulate the alternative splicing of CDKN2A, and the G allele to be related with higher levels of CDKN2A (35).…”
Section: Discussionmentioning
confidence: 76%
“…Considering the role of rs3088440, the C allele has been reported to favour the binding of c-Myb transcription factor to the transcriptional regulatory region of CDKN2A, possibly resulting in its repression and compromise of its normal function in cell cycle (16,29). In turn, the A allele has been found to be possibly associated with an impaired binding of miR-663b to the CDKN2A 3' UTR, leading to an increased expression of p14/p16 proteins (14,30). Therefore, the contribution of the T allele to EC formation seems fairly plausible through the altered binding of transcription factors to the transcriptional regulatory site of CDKN2A.…”
Section: Discussionmentioning
confidence: 99%
“…So far, distinct single nucleotide polymorphisms (SNPs) in CDKN2A (P14ARF) have been correlated with various tumours, like acute lymphoblastic leukaemia (ALL), nasopharyngeal carcinoma, medullary thyroid carcinoma, oropharyngeal cancer, oesophageal squamous cell carcinoma (ESCC), or salivary gland carcinoma (13)(14)(15)(16)(17)(18). The rs3088440 polymorphism, located in the 3' UTR region of CDKN2A, has been shown to be important in the susceptibility to and for the prognosis of several cancers, including HPV16positive oropharynx cancer, melanoma, or squamous cell carcinoma of the head and neck (SCCHN) (14,17,19). Among patients with paediatric B-cell precursor ALL (BCP-ALL), rs3731217 SNP in intron 1 of CDKN2A, has been suggested to influence the risk of cancer, by regulating alternative splicing of CDKN2A, possibly associated with the translation of p16 and p14ARF tumour suppressors ( Figure 1) (20).…”
mentioning
confidence: 99%